Radioglaciological studies on Hurd Peninsula glaciers, Livingston Island, Antarctica - Navarro Valero, Francisco José; Otero García, Jaime; Macheret, Yu; Vasilenko, Evgeniy; Lapazaran Izargain, Javier Jesús; Ahlstrom, L.P.; Machío, F. (E.T.S.I. Telecomunicación (UPM), 2009)
We present the results of several radio-echo sounding surveys carried out on Johnsons and Hurd Glaciers, Livingston Island, Antarctica, between the 1999/2000 and 2004/05 austral summer campaigns, which included both radar profiling and common-midpoint measurements with low (20- 25 MHz)- and high (200MHz)-frequency radars. The latter have allowed us to estimate the radio-wave velocity in ice and firn and the corresponding water contents in temperate ice, which vary between 0 and 1.6% depending on the zone. Maximum ice thickness is ~200 m, with a mean value of 93.6 ± 2.5 m. Total ice volume is 0.968 ± 0.026 km3, for an area of 10.34 ± 0.03 km2. The subglacial relief of Johnsons Glacier is quite smooth, while that of Hurd Glacier shows numerous overdeepenings and peaks. The radar records suggest that Hurd Glacier has a polythermal structure, contrary to the usual assumption that glaciers in Livingston Island are temperate. This is also supported by other dynamical and geomorphological evidence.